2002
DOI: 10.1164/rccm.2012008
|View full text |Cite
|
Sign up to set email alerts
|

The Best Peak Expiratory Flow Is Flow-Limited and Effort-Independent in Normal Subjects

Abstract: Recently, it has been suggested that peak expiratory flow (PEF) may be determined by the wave speed flow-limiting mechanism. In six normal male subjects (age = 33 +/- 8 years) performing expiratory forced vital capacity (FVC) maneuvers, a negative expiratory pressure (NEP) of -10 cm H2O was randomly applied at the beginning of maximal expiration to assess changes in PEF as compared with baseline. During FVC maneuvers, the expiratory effort was measured by changes in esophageal pressure (Pes), as either peak ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 16 publications
1
19
1
1
Order By: Relevance
“…The extrinsic mechanical compression on the lung together with the thorax might also be the leading mechanism of a decreased FEV in our study. Because the PEF is limited by force-velocity characteristics of expiratory muscles instead of mechanical properties of the lung and airways, insufficient force would lead to flow limitation (27).…”
Section: Discussionmentioning
confidence: 99%
“…The extrinsic mechanical compression on the lung together with the thorax might also be the leading mechanism of a decreased FEV in our study. Because the PEF is limited by force-velocity characteristics of expiratory muscles instead of mechanical properties of the lung and airways, insufficient force would lead to flow limitation (27).…”
Section: Discussionmentioning
confidence: 99%
“…k 1 was set proportional to each subject's FEF and k 2 was set to 1.9 for all the subjects. P m was added to the driving pressure from V PEF to the lowest simulated lung volumes, i.e., over the region where flow is limited [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, traditional teaching indicated that early expiration is primarily limited by effort dependent muscle strength. However, a recent model in normal individuals showed that peak expiratory flow was limited by mechanical properties of the lung (in accordance with the wave speed mechanism), and not by muscle strength (Tantucci, C., 2002). As peak flow normally occurs at around 80% of total lung capacity, the wave speed theory can be used to explain expiratory flow limitation from a vital capacity of 80% and less.…”
Section: Wwwintechopencommentioning
confidence: 96%